P53-induced miR-30e-5p inhibits colorectal cancer invasion and metastasis by targeting ITGA6 and ITGB1 - Laudato, Sara; Patil, Nitin; Abba, Mohammed L.; Leupold, Jörg; Gaiser, Timo; Marx, Alexander; Allgayer, Heike (International journal of cancer, 2017)
The tumor suppressor P53 is a critical regulator of normal cellular homeostasis whose function is either distorted or lost in several cancer types including colorectal cancer (CRC). A small group of microRNAs have come to be recognized as essential mediators of P53 function. In a genome-wide systematic approach, we explored miRNAs that are substantially altered by P53 loss and found miR-30e to be the most significantly deregulated miRNA in P53-knockout human CRC cells. We identified miR-30e-5p to be a novel direct transcriptional target of P53 with gain and loss of function experiments revealing miR-30e-5p to be a significant regulator of tumor cell migration, invasion and in vivo metastasis mediated in part by integrins alpha-6 and beta-1 as novel targets. MiR-30e-5p also significantly reduced tumor cell proliferation by causing G1/S cell cycle arrest, which was achieved by inducing P21 and P27 expression. Finally, we found miR-30e-5p to be lost in resected CRC tumors as compared to normal colon tissues. Taken together, miR-30e-5p is a novel effector of P53-induced suppression of migration, invasion and metastasis.
Gesehen am 27.06.2018